Effects of gadolinium-doping on the structural, thermal, and spectroscopic properties of zinc-based hydroxyapatites - Ates, Tankut; Cretin, Burhan Tarik; Goldberg, Margarita A.; Allame, Sara Sabah Khaeoon; Donskaya, Nadezhda O.; Fomin, Alexander S.; Kaygili, Omer (Elsevier Sci Ltd, 2026)
This study examines how increasing gadolinium (Gd) content influences the structural, electronic, thermal, and biological properties of zinc-based hydroxyapatite (HAp) synthesized by a wet chemical method and supported by DFT modeling. Co-doping with Gd alters the HAp/beta-TCP phase ratio, induces detectable changes in lattice parameters, crystallite size, and microstrain, and is in excellent agreement with theoretical predictions. DFT calculations show a systematic bandgap reduction from 4.5154 to 4.3136 eV with rising Gd concentration, demonstrating that rare-earth incorporation effectively tunes the electronic structure of HAp. FTIR and Raman analyses confirm the preservation of characteristic phosphate and hydroxyl vibrational modes, while thermal analysis indicates high stability up to 900 degrees C. SEM/EDX results show morphology and composition shifts with dopant level. Cell viability tests reveal strong biocompatibility for all samples except the highest Gd-doped formulation. Overall, Zn-Gd co-doping provides a robust strategy for engineering multifunctional bioceramics.
Keywords: Hydroxyapatite (HAp); Bandgap; Thermal stability; In vitro biocompatibility